Penerapan Program Lapak Buku untuk Meningkatkan Minat Baca Siswa SMKN 1 Kotaraja - Aidiatul Fitri, Ramdani; Rochmi, Evilia; Yanti, Nila; Utami, Desy Auliya; Fitriani, Nurlailina; Hamid, Muhammad (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
The implementation of the Book Stall Program at SMKN 1 Kotaraja was driven by the low reading interest among students, reflected in the limited use of the school library and minimal participation in literacy activities. This condition indicated the need for a literacy strategy that is accessible, appealing, and integrated into students’ daily routines. Through a teaching assistance approach, the program was designed to create an open literacy space that allows students to interact freely with various reading materials. The method was carried out twice a week in the school’s outdoor area, using mentoring, interpersonal communication, and direct observation to capture students’ levels of engagement. The findings indicate a clear increase in students’ reading interest, as shown by their spontaneous visits to the book stall, willingness to browse and read books, active discussions about the content, and repeated participation in subsequent sessions. Students also demonstrated greater confidence in expressing their understanding and showed improvement in communicative and reflective literacy behaviors. These results highlight that open reading spaces, consistent exposure to books, and supportive mentoring can effectively stimulate students’ interest in reading. Therefore, the Book Stall Program supported by teaching assistance contributes positively to fostering a sustainable literacy culture in SMKN 1 Kotaraja.